Aesthetics of Style in the Poetical Collection of “Insomnia Party” by Aisha Al-Nowaimi - Al-Zahrani, Asma Abdullah Abdul Khaleq (Arts for Linguistic & Literary Studies, 2024)
This study delves into the stylistic aesthetics present in the poetry collection "Insomnia Party" by Aisha Al-Nowaimi. Comprising an introduction, preface, two main sections, and findings, the research aims to elucidate the aesthetic framework underpinning the analyzed work. The introduction lays the groundwork by defining key aesthetic concepts guiding the study. The initial section explores linguistic-stylistic elements such as linguistic formation, stylistic structures, and interrelation forms. The subsequent section delves into the aesthetics of significance, examining the relationship between composition and imagery, while addressing themes like negation, repetition, poetic vision, feminist perspective, and pictorial structure. Employing a stylistic approach for analysis, the research uncovers several insights. For instance, it observes that the collection's title paradox permeates its poetic discourse, indicating the poet's intention to employ a dialogic language devoid of excessive lyricism, thus emphasizing textual specificity. Furthermore, the poet's innovative use of dissonance, paradox, and symbolic intensity challenges traditional connotations within the poetic domain.